Connecting agricultural robots and smart implements by using ISO 11783 communication. Issue 32 (2022) - Paraforos, Dimitrios S.; Aubé, Cristophe; Athanasakos, Loukas; Avgoustakis, Ioannis; Baron, Suzanne; Bresilla, Trim; Fountas, Spyros; Hemming, Jochen; Karagiannis, Panagiotis; Mylonas, Nikos; Nieuwenhuizen, Ard T.; Garcia, Ferran Roure; et al.
Abstract: Agriculture is facing many challenges that are related to increased prices of farming inputs, labor shortage, and climate change. Advanced machines and autonomous vehicles as well as sensor systems with increased capabilities are now present on the farm and can offer solutions to these challenges but the issue that remains is how to connect the components involved in forming an integrated digital farming system. At the same time, ISO 11783 (commonly designated as ISOBUS) is playing a substantial role in farming and an increasing number of ISOBUS-compliant machines can be seen among the farm machinery. Under this perspective, the newly funded H2020 project Robs4Crops is trying to combine agricultural robotics with the already existing implements by leveraging ISOBUS. The aim is to integrate autonomous vehicles into the available farm infrastructure and not include them as proprietary solutions. In addition, the project aims at increasing the intelligence of the implements by using sensors and analytics that in real-time can assess the efficiency of the operation performed and subsequently, by using ISOBUS, inform the robots in order for the latter to take relevant action. This work describes the development of perception units for spraying and mechanical weeding machines and how these "intelligent" implements are using ISOBUS to communicate with two different agricultural robots. From the existing results, it is becoming clear that ISOBUS can play an important role in introducing agricultural robots in farming but also facilitate the cyber-physical connection between the implements and the cloud-based solutions (e.g. digital twins).